Microbioreactor Cultivations of Fab‐Producing Escherichia coli Reveal Genome‐Integrated Systems as Suitable for Prospective Studies on Direct Fab Expression Effects. Issue 11 (26th July 2019) - Fink, Mathias; Vazulka, Sophie; Egger, Esther; Jarmer, Johanna; Grabherr, Reingard; Cserjan‐Puschmann, Monika; Striedner, Gerald
Abstract : Despite efforts to develop concepts for efficient antibody fragment (Fab) production in Escherichia coli ( E. coli ) and the high degree of similarity within this protein class, a generic platform technology is still not available. Indeed, feasible production of new Fab candidates remains challenging. In this study, a setup that enables direct characterization of host cell response to Fab expression by utilizing genome‐integrated (GI) systems is established. Among the multitude of factors that influence Fab expression, the variable domain, the translocation mechanism, the host strain, as well as the copy number of the gene of interest (GOI) are varied. The resulting 32 production clones are characterized in carbon‐limited microbioreactor cultivations with yields of 0–7.4 mg Fab per gram of cell dry mass. Antigen‐binding region variations have the greatest effect on Fab yield. In most cases, the E. coli HMS174(DE3) strain performs better than the BL21(DE3) strain. Translocation mechanism variations mainly influence leader peptide cleavage efficiency. Plasmid‐free systems, with a single copy of the GOI integrated into the chromosome, reach Fab yields in the range of 80–300% of plasmid‐based counterparts. Consequently, the GI Fab production clones could greatly facilitate direct analyses of systems response to different impact factors under varying production conditions. Abstract : The production of antibody fragments (Fab) in Escherichia coli is challenging. In this study, periplasmic Fab expression systems with varying influence factors on growth and yield are investigated in carbon‐limited microbioreactor cultivations. Systems with one genome‐integrated gene copy are benchmarked against conventional plasmid‐based systems. It turns out that genome‐integrated clones facilitate direct characterization of Fab‐driven effects on host cell metabolism.